Update on the efficacy, safety, and adherence to treatment of full length parathyroid hormone, PTH (1-84), in the treatment of postmenopausal osteoporosis - Luca Pietrogrande (Dove Medical Press, 2009)
Luca PietrograndeDipartimento di Medicina Chirurgia e Odontoiatria Polo San Paolo, Università degli Studi di Milano, Milan, ItalyAbstract: Full length (1-84) parathyroid hormone (PTH) was introduced in Europe as a treatment for postmenopausal osteoporosis in 2006. The efficacy of PTH (1-84) in the prevention of vertebral fractures is very high, and is similar to that of teriparatide. Its action in the prevention of femoral fractures has yet to be fully demonstrated, but the incidence of such fractures in trials was very low, and a decrease in nonvertebral fractures was seen in high-risk patients. The effect on bone mineral density (BMD) was clearly demonstrated in the spine and also in the hip. The effects on BMD were evident and increased progressively with treatment until 36 months. After its discontinuation there was a clear decrease in BMD if no antiresorptive treatment was initiated. Increases in bone volumetric density and bone volume in trabecular sites were also reported. Moreover, a bone volume increase was detected in cortical sites. Hypercalcemia and hypercalciuria are frequent consequences of PTH treatment, but rarely have clinical effects and are usually well controlled by reducing calcium and vitamin D supplementation.Keywords: PTH (1-84), full-length parathyroid hormone, osteoporosis treatment